2019
DOI: 10.1371/journal.pone.0224083
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding gambling harm: An evidence-based set of safe gambling practices for consumers

Abstract: Prior studies have identified self-regulatory strategies that are infrequently used by problem-gamblers, but which might be protective if used. However, guidelines with evidence-based safe gambling practices (SGPs) that prevent gambling-related harm are lacking. This study aimed to: 1) identify a parsimonious set of evidence-based SGPs that best predict non-harmful gambling amongst gamblers who are otherwise most susceptible to experiencing gambling harm; 2) examine how widely are they used; and 3) assess whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…50 Recent data have focused on the potential for the reduction of gamblingrelated harm if gamblers adopt a range of safe gambling practices, such as a budget and a preset limit of how much one can afford to lose, not borrowing money in order to gamble, not using gambling as a part of emotional control, and alternative activities. 51 Consumer credit applications have been suggested as a window of opportunity to screen for problematic gambling, 52 and may be more common in problematic gambling than in non-problematic gambling. 53 "Chasing losses" behavior, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recent data have focused on the potential for the reduction of gamblingrelated harm if gamblers adopt a range of safe gambling practices, such as a budget and a preset limit of how much one can afford to lose, not borrowing money in order to gamble, not using gambling as a part of emotional control, and alternative activities. 51 Consumer credit applications have been suggested as a window of opportunity to screen for problematic gambling, 52 and may be more common in problematic gambling than in non-problematic gambling. 53 "Chasing losses" behavior, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two studies include data on age, and several of these found that being younger was associated with a higher risk of experiencing gambling harms [39][40][41][42][43][44] . In particular one study found that younger age groups (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were at risk of dependence and social harms 39 , and Ferrara et al 42 found that as well as higher rates of what they label "problematic gambling", younger age groups showed a higher comorbidity with other addictions. In…”
Section: Agementioning
confidence: 99%
“…Despite this body of research, and many individual studies investigating speci c gambling harms, a systematic review of how harms are distributed across society hasn't yet been done. Although many studies have investigated how harms can be minimised [17][18][19] , a complete understanding of the disease and its impact on society is dependent on understanding how harms are distributed across the population.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two studies include data on age, and several of these found that being younger was associated with a higher risk of experiencing gambling harms [39][40][41][42][43][44] . In particular one study found that younger age groups (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were at risk of dependence and social harms 39 , and Ferrara et al 42 found that as well as higher rates of what they label "problematic gambling", younger age groups showed a higher comorbidity with other addictions.…”
Section: Agementioning
confidence: 99%